Analysis of Financial Report Auditor Planning in Government Internal Control - Azaluddin, Azaluddin (Institute for Research and Community Service, 2022)
This study aims to determine the suitability of Planning Auditor of the Financial Statements of the Buton Regency Inspectorate, with Standard Audit of Government Internal Supervisory Apparatus implemented by BPK-RI. The research method used is descriptive with a approach the research was conducted at the Inspectorate Office of Buton Regency, which is located in Southheast Sulawesi Province. The research was carried out on August 2 to September 2, 2022. The result of this research is that the planning for the audit of the financial statements at the Buton district Inspectorate office has complied with the audit standards of the government’s internal supervisory apparatus implemented by the financial audit agency of the Republic of Indonesia (BPK-RI). The audit standard applies 3 statements of Field Work Standards (SPAP) set by the Indonesian Accountants Association, namely: 1) Work must be planned as well as possible and if used assistants must be properly supervised 2) A sufficient understanding of intern control must be obtained to plan the audit and determine the nature and scope of the tests to be performed 3) Competent audit evidence must be obtained through inspection, observation, submission of statements, and confirmations as a reasonable basis for expressing an opinion on the audited financial statements.